2015
DOI: 10.1111/jvs.12353
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the hydrological niche: soil moisture, space and lifespan

Abstract: Summary 201. Niche segregation on fine-scale soil-moisture gradients is found in many plant 21 communities, but the contribution of this to community structure has yet to be analysed 22 in a fully spatial manner. We introduce a univariate and multivariate analytical 23 approach that, taking spatial autocorrelation into account, decomposes the spatial 24 structure of species composition into components that correlate with linear and non-25 linear soil-moisture gradients plus a residual. 26 2. The analysis is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…Following Hutchinson, a species' fundamental niche space is narrowed to a realized niche by interspecific competition and natural enemies (Silvertown 2004). More recently, hydrological gradients have been studied extensively, and interspecific differentiation in niches has been further demonstrated (Silvertown et al 1999; Bartelheimer et al 2010;Araya et al 2011;García-Baquero et al 2016). From an ecophysiological viewpoint, this clear separation of species can be explained in terms of the challenges plants face along the hydrological gradient.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
“…Following Hutchinson, a species' fundamental niche space is narrowed to a realized niche by interspecific competition and natural enemies (Silvertown 2004). More recently, hydrological gradients have been studied extensively, and interspecific differentiation in niches has been further demonstrated (Silvertown et al 1999; Bartelheimer et al 2010;Araya et al 2011;García-Baquero et al 2016). From an ecophysiological viewpoint, this clear separation of species can be explained in terms of the challenges plants face along the hydrological gradient.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 96%
“…A key difficulty with measuring both niche availability for single species and niche partitioning among species is that the measurements often rely on identifying the relevant axes along which species might differ in their niche requirements (Silvertown & Law, ; Tilman, ). While there is strong evidence that niche partitioning along environmental gradients allows species to co‐occur (García‐Baquero, Silvertown, Gowing, & Valle, ; Pickett & Bazzaz, ; Rees, ; Tilman, ), co‐occurring species often also show substantial niche overlap (Berdugo et al., ; Mahdi, Law, & Willis, ). Species with niches that appear to overlap along a specific gradient may co‐occur because one or both species is dispersal limited (Soberon, ), but might also co‐occur because they partition niches along other, unidentified niches axes (Silvertown, ).…”
Section: Introductionmentioning
confidence: 99%
“…by C3, C4 and CAM phytosynthesis (Keeley 1998) and in this way enable temporarily coexisting guilds (Angert et al 2009) or coexistance in spatially partitioned hydrological niches (Ellenberg 1953;García-Baquero et al 2015;Silvertown et al 2015). It has been shown that niche partitioning in local moisture gradients contributes importantly to plant diversity (Bauder 2000;Violle et al 2010).…”
mentioning
confidence: 99%
“…This is important because most plants grow separately in local gradients (e.g. García-Baquero, Silvertown, Gowing, & Valle 2015) and perceive varying risk levels according to their niche boundaries.…”
mentioning
confidence: 99%
See 1 more Smart Citation